Role of Notch2 pathway in mature B cell malignancies - Mesini, Nicolò; Fiorcari, Stefania; Atene, Claudio Giacinto; Maffei, Rossana; Potenza, Leonardo; Luppi, Mario; Marasca, Roberto (Frontiers in Oncology, 2023)
In recent decades, the Notch pathway has been characterized as a key regulatory signaling of cell-fate decisions evolutionarily conserved in many organisms and different tissues during lifespan. At the same time, many studies suggest a link between alterations of this signaling and tumor genesis or progression. In lymphopoiesis, the Notch pathway plays a fundamental role in the correct differentiation of T and B cells, but its deregulated activity leads to leukemic onset and evolution. Notch and its ligands Delta/Jagged exhibit a pivotal role in the crosstalk between leukemic cells and their environment. This review is focused in particular on Notch2 receptor activity. Members of Notch2 pathway have been reported to be mutated in Chronic Lymphocytic Leukemia (CLL), Splenic Marginal Zone Lymphoma (SMZL) and Nodal Marginal Zone Lymphoma (NMZL). CLL is a B cell malignancy in which leukemic clones establish supportive crosstalk with non-malignant cells of the tumor microenvironment to grow, survive, and resist even the new generation of drugs. SMZL and NMZL are indolent B cell neoplasms distinguished by a distinct pattern of dissemination. In SMZL leukemic cells affect mainly the spleen, bone marrow, and peripheral blood, while NMZL has a leading nodal distribution. Since Notch2 is involved in the commitment of leukemic cells to the marginal zone as a major regulator of B cell physiological differentiation, it is predominantly affected by the molecular lesions found in both SMZL and NMZL. In light of these findings, a better understanding of the Notch receptor family pathogenic role, in particular Notch2, is desirable because it is still incomplete, not only in the physiological development of B lymphocytes but also in leukemia progression and resistance. Several therapeutic strategies capable of interfering with Notch signaling, such as monoclonal antibodies, enzyme or complex inhibitors, are being analyzed. To avoid the unwanted multiple “on target” toxicity encountered during the systemic inhibition of Notch signaling, the study of an appropriate pharmaceutical formulation is a pressing need. This is why, to date, there are still no Notch-targeted therapies approved. An accurate analysis of the Notch pathway could be useful to drive the discovery of new therapeutic targets and the development of more effective therapies.